The fine line between familial and polygenic hypercholesterolemia. (June 2013) - De Castro-Orós, Isabel; Pocoví, Miguel; Civeira, Fernando
Evaluation of: Talmud PJ, Shah S, Whittall R et al. Use of low-density lipoprotein cholesterol gene score to distinguish patients with polygenic and monogenic hypercholesterolaemia: a case–control study. Lancet 381(9874), 1293–1301 (2013) . Familial hypercholesterolemia (FH) is a common disorder caused by mutations in LDLR, APOB and PCSK9 . However, many subjects with primary hypercholesterolemia did not demonstrate functional mutations in any of these genes. Genome-wide association studies have identified single nucleotide polymorphisms that influence the variability of LDL-C concentration. Talmud et al. have genotyped 12 common LDL cholesterol (LDL-C)-raising alleles in 640 patients with the clinical diagnosis of FH and in 3020 healthy subjects from the UK Whitehall II study. Approximately 50% of the FH patients did not possess a causative mutation and the mean weighted LDL-C gene score was significantly higher than in the controls, indicating a polygenic cause for their disorder. These results indicate that clinical criteria used for FH diagnosis are poorly specific for FH, largely overlapping with polygenic hypercholesterolemia. The 12 single nucleotide polymorphisms LDL-C gene score might be a good tool for distinguishing between monogenic and polygenic hypercholesterolemia.